Lime application reduces potassium and nitrate leaching on sandy soils - Babak Motesharezadeh; Richard Bell; Qifu Ma (Journal für Kulturpflanzen, 2021)
Potassium (K) leaching is common in light-textured soils and reduces soil available K to plants. This study examined the effect of lime application and K rates (nil, 20, 60 kg K/ha) on K leaching and other leachate parameters of four sandy soils in Western Australia. Three out of four soils did not differ in K leaching between the rates of nil and 20 kg K/ha, whereas 60 kg K/ha increased K leaching in all four soils. For the Merredin soils, lime application markedly delayed K leaching at 60 kg K/ha, showing K leaching peak at 4.75 pore volume (PV) in the limed soil (pHCaCl2: 6.20) but at 3 PV in the non-limed soil (pHCaCl2: 4.50), and liming also reduced total amount of leached K and NO3. Similarly, the peak of K leaching occurred at 2–3 PV in the other two non-limed soils. Maximum leachate NO3 concentrations at 60 kg K/ha were 46 mg/L at 2 PV with lime versus 110 mg/L at 1.25 PV without lime, while the amount of leached NO3 from nil K soils was greater than from the K treated soils. The results suggest that liming of an acid sand can slow down and reduce K and NO3 leaching and have significant implication for K-fertilizer management on such soils.